2015
DOI: 10.1093/rheumatology/kev294
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory and autoimmune manifestations associated with myelodysplastic syndromes and chronic myelomonocytic leukaemia: a French multicentre retrospective study

Abstract: The spectrum of SIADs associated to MDS is heterogeneous, steroid sensitive, but often steroid dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(203 citation statements)
references
References 23 publications
11
183
2
7
Order By: Relevance
“…No previous studies focused on CMML-associated SAIDs treatment and outcomes, and response rates to steroids alone was similar comparing to our larger cohort of MDS-associated SAIDs (80%) (3). Despite this initial good response, 40% of patients needed a second-line treatment for relapse or steroid dependence, comparing to 48% in other MDS-associated SAIDs (3).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…No previous studies focused on CMML-associated SAIDs treatment and outcomes, and response rates to steroids alone was similar comparing to our larger cohort of MDS-associated SAIDs (80%) (3). Despite this initial good response, 40% of patients needed a second-line treatment for relapse or steroid dependence, comparing to 48% in other MDS-associated SAIDs (3).…”
Section: Discussionsupporting
confidence: 70%
“…CPSS score was 0 (n=6, 37.5%), 1 (n= 6, 37.5%), 2 or 3 (n=3, 19%), and 4 (n=1, 6%) ( Table 1). According to the French-American-British classification of CMML, 55% of patients had a myelodysplastic form (WBC <13000 /mm 3 ) and 45% a myeloproliferative form (WBC >13000 /mm 3 ).…”
Section: Cmml and Saids Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Association with inflammatory myopathies has been very rarely described (8)(9)(10)(11)(12)(13)(14)(15). In particular, in the case report published by Tsuji et al, antinuclear antigens were found, but the assay for anti-Jo1, RNP and Scl70 resulted negative.…”
Section: Case Reportmentioning
confidence: 99%
“…Bei anderen Non-Hodgkin-Lymphomen (NHL) und auch beim Morbus Hodgkin wurde in Einzelberichten neben Arthralgien und Myalgien auch eine eosinophile Fasziitis, eine Arthritis oder Gelenkinfiltration mit Tumorzellen beschrieben [9,31]. Etwa ein Drittel der Arthritiden lag dabei als Polyarthritis vor, und bei ca.…”
Section: Introductionunclassified